Using Six Sigma Methodology to Improve the Assembly Process in an Automotive Company. (7th June 2016) - Pugna, Adrian; Negrea, Romeo; Miclea, Serban
Abstract: The exigencies of the permanently evolving markets require continuous adaptation of company offers. The development and continuous improvement of the quality and environment management systems would be to anticipate these developments and therefore fully satisfy the needs and expectations of each partner (customers, staff and other stakeholders) and also maintain competitive advantage. One of the possibilities of gaining operational excellence is implementing different quality improvement initiatives like Total Quality Management, ISO certification, Agile & Lean manufacturing etc. Real life demonstrated that these initiatives are neither time efficient nor profitable in terms of quality. Therefore introducing and implementing the Six Sigma methodology was proven to provide breakthrough quality improvements in a reasonable short time. This paper presents a creative solution for improving an assembly process in an automotive company in Romania by using Statistical Thinking and DMAIC Six Sigma methodology.